1973
DOI: 10.1136/bmj.3.5870.28
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation in Fabry's disease.

Abstract: The right abducens nerve palsy gradually improved. Six weeks after discharge lateral movement of the right eye was apparently full but the diplopia persisted and he complained of blurring in the left eye. Prednisolone was then given, but a week later vision in the right eye became blurred. The left carotid and the left radial pulses were absent and the right carotid pulse was weak. A short, soft systolic bruit was audible over the right carotid artery. Visual impairment was believed to be due to retinal ischae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Lockman et al (1973) in a double-blind crossover study, have shown the beneficial use of diphenylhydantoin in this condition. During the past few years several patients with Anderson-Fabry's disease in end-stage renal failure have received renal transplants (Desnick et al, 1972;Philippart, Franklin, and Gordon, 1972;Clarke et al, 1972;Biihler et al, 1973). Apart from the aimed benefit from improved renal function, attempts at renal transplantation were also seriously pursued because of possible general improvement following the production by the transplanted kidney of the deficient a-galactosidase enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Lockman et al (1973) in a double-blind crossover study, have shown the beneficial use of diphenylhydantoin in this condition. During the past few years several patients with Anderson-Fabry's disease in end-stage renal failure have received renal transplants (Desnick et al, 1972;Philippart, Franklin, and Gordon, 1972;Clarke et al, 1972;Biihler et al, 1973). Apart from the aimed benefit from improved renal function, attempts at renal transplantation were also seriously pursued because of possible general improvement following the production by the transplanted kidney of the deficient a-galactosidase enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…No information is mentioned about the GLA mutation involved. Histology shows typical endothelial, interstitial and glomerular deposits (multilamellar bodies, sphingolipid inclusions) in 6 to 11 cases ( Table 2 ) [ 21 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. It was not clear whether the occurrence of the ceramide accumulation in the renal graft could add further risk of graft failure.…”
Section: Recurrence Of Fabry Disease In Kidney Transplantation: Thmentioning
confidence: 99%
“…Kidney transplantation has been effective in treating renal disease but does not reverse the disease manifestations in other organs. 36 Two recent clinical trials have shown efficacy of enzyme replacement with recombinant α-galactosidase A. Schiffmann et al 37 reported improvement of neuropathic pain and stabilization of renal function in 26 affected men treated for 6 months. In a second study, α-galactosidase A therapy decreased renal microvascular endothelial deposits in the kidney, skin, and heart within 20 weeks of treatment but unfortunately was ineffective for neuropathic pain.…”
Section: Fabry Diseasementioning
confidence: 99%